GE_GERICHTE C/18451/2016 vom 29. Januar 2019 - GE Cour de justice (2019)
ACTION EN PAIEMENT D'ENTRETIEN ; ACTION EN MODIFICATION ; OBLIGATION D'ENTRETIEN ; ENFANT ; MAJORITÉ(ÂGE) | CC.276; CPC.317.al2; CPC.261.al1; CPC.316.al3; CC.286.al2; CC.285.al1; CC.277.al1